Nanosensors : theory and applications in industry, healthcare, and defense - Lim, Teik-Cheng (CRC Press, 2011)
"Nanosensors, sensing devices with at least one sensing dimension less than 100nm, have become instrumental for monitoring physical and chemical phenomena, detecting biochemicals in cellular organelles, and measuring nanoscopic particles in industrial processes. This book provides a guide to nanosensors. Inspired by his own experience with nanofiber-based gas sensors, the author explains the principles and applications of nanosensors for industry, healthcare, and defense. Each chapter presents an overview of the specific type of nanosensor and then describes the fundamental science that forms the basis of the sensing mechanism, fabrication techniques, and the specific nanosensor's detection"--